Genetic analysis of the Arabidopsis protein kinases MAP3Kε1 and MAP3Kε2 indicates roles in cell expansion and embryo development - Chaiwongsar, Suraphon; Strohm, Allison; Su, Shih-Heng; Krysan, Patrick J. (Frontiers in Plant Science, 2012)
MAP3Kε1 and MAP3Kε2 are a pair of Arabidopsis thaliana genes that encode protein kinases related to cdc7p from Saccharmomyces cerevisiae. We have previously shown that the map3kε1;map3kε2 double-mutant combination causes pollen lethality. In this study, we have used an ethanol-inducible promoter construct to rescue this lethal phenotype and create map3kε1-/-;map3kε2 -/- double-mutant plants in order to examine the function of these genes in the sporophyte. These rescued double-mutant plants carry a YFP-MAP3Kε1 transgene under the control of the alcohol-inducible AlcA promoter from Aspergillus nidulans. The double-mutant plants were significantly smaller and had shorter roots than wild-type when grown in the absence of ethanol treatment. Microscopic analysis indicated that cell elongation was reduced in the roots of the double-mutant plants and cell expansion was reduced in rosette leaves. Treatment with ethanol to induce expression of YFP-MAP3Kε1 largely rescued the leaf phenotypes. The double-mutant combination also caused embryos to arrest in the early stages of development. Through the use of YFP reporter constructs we determined that MAP3Kε1 and MAP3Kε2 are expressed during embryo development, and also in root tissue. Our results indicate that MAP3Kε1 and MAP3Kε2 have roles outside of pollen development and that these genes affect several aspects of sporophyte development.